Learning to work from home: experience of Australian workers and organizational representatives during the first Covid-19 lockdowns. Issue 3 (7th June 2021) - Marzban, Samin; Durakovic, Iva; Candido, Christhina; Mackey, Martin
Abstract : Purpose: This paper aims to provide a snapshot of workers' experience while working from home (WFH) during the Australian lockdown in the middle of the Covid-19 pandemic. It focuses on lessons to inform organizations, employees and the design of the workspaces post-2020, human, organizational and environmental considerations may affect satisfaction, productivity and health. Design/methodology/approach: Two separate surveys were designed for this study to target Australian organizations and knowledge workers. Participants included 28 organizations and 301 employees, and descriptive and correlational analyses were conducted. Findings: Organizations stated productivity losses, maintaining culture and workplace health and safety concerns with WFH setup while employees were more concerned about their social interactions, internet connectivity and increased workload. Employees also found the social aspects of WFH challenging and disclosed that face-to-face interactions with their colleagues was the most important reason they wanted to return to the office. High level of trust and value was reported amongst the organizations and workers. Originality/value: In the scarcity of academic literature around negative and positives of the WFH experiment during the COVID-19 pandemic, the main sources of information have been industry-focused reports. This study aims to contribute to this knowledge gap by identifying positives and negative aspects of WFH during the first wave of lockdowns in Australia in 2020 from the organization and workers' perspective, including human, organizational and environmental considerations.